Probiotic-derived extracellular vesicles: the next breakthrough in postbiotics for rheumatoid arthritis - Dell’Atti, Federica; Abreu, Hugo; Malfa, Patrizia; Raineri, Davide; Cappellano, Giuseppe; Chiocchetti, Annalisa (Frontiers in Immunology, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by systemic inflammation and joint damage. Emerging evidence highlights the role of gut and oral microbiota in RA pathogenesis, with microbial dysbiosis potentially exacerbating inflammation and immune dysregulation. Although probiotics have shown potential in modulating the oral and gut microbiota and improving RA symptoms, a promising cell-free substitute is provided by postbiotics, including probiotic-derived extracellular vesicles (EVs). These bioactive nanoparticles transport functional metabolites capable of modulating immune responses, reducing inflammation, and restoring gut barrier integrity. Probiotic-derived EVs are, for instance, able to promote M2 macrophage polarization and suppress pro-inflammatory cytokines, thus highlighting their therapeutic potential. Nonetheless, challenges remain in standardizing EVs production, optimizing administration routes, and ensuring clinical safety. The targeting and effectiveness of probiotic EVs may be improved by developments in omics sciences and biotechnology techniques, making them the next breakthrough in postbiotics for the treatment of RA. This review examines how probiotic-derived EVs interact with the host, focusing on their crosstalk with immune cells and subsequent immune modulation. We highlight their potential for RA treatment, discuss clinical challenges, and explore their use in personalized medicine.